Surviving in the Hot-Neptune Desert: The Discovery of the Ultrahot Neptune TOI-3261b - Nabbie, Emma (2024)
The recent discoveries of Neptune-sized ultra-short-period planets (USPs) challenge existing planet formation theories. It is unclear whether these residents of the Hot Neptune Desert have similar origins to smaller, rocky USPs, or if this discrete population is evidence of a different formation pathway altogether. We report the discovery of TOI-3261b, an ultrahot Neptune with an orbital period P = 0.88 day. The host star is a V = 13.2 mag, slightly supersolar metallicity ([Fe/H] ≃0.15), inactive K1.5 main-sequence star at d = 300 pc. Using data from the Transiting Exoplanet Survey Satellite and the Las Cumbres Observatory Global Telescope, we find that TOI-3261b has a radius of 3.82‑0.35+0.42 R ⊕. Moreover, radial velocities from ESPRESSO and HARPS reveal a mass of 30.3‑2.4+2.2 M ⊕, more than twice the median mass of Neptune-sized planets on longer orbits. We investigate multiple mechanisms of mass loss that can reproduce the current-day properties of TOI-3261b, simulating the evolution of the planet via tidal stripping and photoevaporation. Thermal evolution models suggest that TOI-3261b should retain an envelope potentially enriched with volatiles constituting ∼5% of its total mass. This is the second highest envelope mass fraction among ultrahot Neptunes discovered to date, making TOI-3261b an ideal candidate for atmospheric follow-up observations.